Prevalência e intensidade de infecção por Batrachochytrium dendrobatidis em população de Boana cf. curupi - Toscan, Jonas Ricardo (2020)
Worldwide, anurans have suffered from extinctions and population declines caused by several factors, one of which is the chytridiomycosis, an emerging infectious disease caused by Batrachochytrium dendrobatidis (Bd), present in all continents where anurans occur, including in the Brazilian Atlantic Forest where it is widely disseminated. Many biotic and abiotic factors are highly relevant to the risk of infection and the lethality of the pathogen. Thus, this study aims to verify the prevalence and intensity of fungal infection in Boana cf. curupi, an endangered species in Brazil categorized as “vulnerable” by ICMBIO, in order to find correlations between fungal infection and environmental variables, as well as verifying the influence of infection on individuals' body condition by the “Scalar Mass Index” (SMI). The sampling was carried out on a stretch of stream within a forest fragment in the municipality of Dois Vizinhos - Paraná, from December 2018 to November 2019, using an active search with marking and recapture of individuals to collect samples of mycotic material with the use of swabs. The environmental variables sampled were temperature, flow rate, nitrate content and water pH, as well as humidity and air temperature. The CRC and weight of individuals were acquired to obtain the SMI. The samples were subjected to qPCR for the detection and quantification of Bd. As a result, 125 individuals were sampled, of which 56.8% (n = 71) were recaptured one or more times. The fungus infection was found in all months in the period, and the prevalence found was 4.4% (n = 15 samples). There was a weak correlation between the infection and all the variables analyzed. Negative variations were observed in the SMI of infected individuals, with a moderate negative correlation with air temperature, and a moderate positive correlation with nitrate content, pH, season and intensity of infection. We confirm that the fungus is also present in this population and that visually there are negative variations in the SMI of infected individuals. However, it is unlikely that B. cf. curupi is developing chytridiomycosis, there are possibly cofactors that also contribute to the SMI variation. More in-depth studies of the relationship of this infection with these hosts are needed to verify possible declines in this population, in addition to contributing to the understanding of the dynamics of this pathology.